2021
DOI: 10.1021/acs.biomac.1c01230
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Designing Particle-Regulated Amyloid-like Assembly of Synthetic Polypeptides in Aqueous Solution

Abstract: In cells, actin and tubulin polymerization is regulated by nucleation factors, which promote the nucleation and subsequent growth of protein filaments in a controlled manner. Mimicking this natural mechanism to control the supramolecular polymerization of macromolecular monomers by artificially created nucleation factors remains a largely unmet challenge. Biological nucleation factors act as molecular scaffolds to boost the local concentrations of protein monomers and facilitate the required conformational cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Unlike PGlu and most homopolypeptides, PLys can transform into hydrogels, consisting of elongated nanofibrils, when the side-chain charges neutralize under alkaline conditions (Figure S1). This transformation is notably rapid and devoid of the typical nucleation lag phases often seen in amyloid-like supramolecular assemblies. , Given Ser’s propensity for β-sheet structures and its increased hydrophilicity compared to Glu in acidic environments where self-assembly occurs, it is anticipated to act as a catalyst in the formation of widespread, elongated fibrils. At sufficiently high concentrations, these copolypeptide fibrils are likely to intertwine swiftly to form a sample-spanning network, overcoming the stacking challenges of PGlu fibrils and offering a cohesive and stable hydrogel structure, circumventing precipitation constraints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike PGlu and most homopolypeptides, PLys can transform into hydrogels, consisting of elongated nanofibrils, when the side-chain charges neutralize under alkaline conditions (Figure S1). This transformation is notably rapid and devoid of the typical nucleation lag phases often seen in amyloid-like supramolecular assemblies. , Given Ser’s propensity for β-sheet structures and its increased hydrophilicity compared to Glu in acidic environments where self-assembly occurs, it is anticipated to act as a catalyst in the formation of widespread, elongated fibrils. At sufficiently high concentrations, these copolypeptide fibrils are likely to intertwine swiftly to form a sample-spanning network, overcoming the stacking challenges of PGlu fibrils and offering a cohesive and stable hydrogel structure, circumventing precipitation constraints.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier-transform infrared spectra (FTIR) and wide-angle X-ray diffraction (WAXD) of the fibrils revealed that they were primarily composed of β-sheet structures (Figure S16 and S17). The kinetics of fibrillation were examined using thioflavin T (ThT) , in a 15 mM acetate buffer (pH 4), monitoring the enhanced fluorescence emission upon ThT’s binding to β-sheet structures. TEM analysis confirmed that the fibril morphologies remained consistent in the presence of an acetate buffer (Figure S23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] The past two decades have witnessed significant advancements in polypeptide solution self-assembly, which have been summarized by several groups so far. [13][14][15][16] Recently, some remarkable advances have been achieved in the solution self-assembly of polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of polypeptide self‐assembly systems, including homopolymers, block and graft copolymers, and multi‐component systems, have been studied 10–12 . The past two decades have witnessed significant advancements in polypeptide solution self‐assembly, which have been summarized by several groups so far 13–16 …”
Section: Introductionmentioning
confidence: 99%